Physiotherapy rehabilitation management on phase IV of post-operative anterior cruciate ligament reconstruction with medial meniscus repair : a case report - Ni Putu Sukma Nathania; Putu Rara Kumbhara Vigneswari; Rizki Cristine Hasibuan; Iwan Kurnia Susanto (Kinetic and Physiotherapy Comprehensive, 2023)
Background: Sports injuries are injuries that arise as a result of sporting activities or activities. 60% of sports-related injuries occur in the lower limbs, including the knee's anterior cruciate ligament (ACL). This study aims to evaluate the physiotherapy interventions to improve ROM, balance, and knee function following ACLR with medial meniscus repair phase IV.   Case Description: The patient complained of pain and stiffness in the popliteal area. The pain was felt when driving a car and squatting. The injury occurred when playing futsal, and the patient made a zigzag while trying to win the ball. The patient took the wrong footing. Namely, the body turned while the left leg was left behind, and the knee joint suddenly rotated or twisted. Before surgery, the patient had carried out physiotherapy for six meetings. The operation was carried out on 11 May 2022 at the Royal Progress Hospital with three-day hospitalisation. The patient has been doing physiotherapy since the first day after surgery. Currently, the patient has entered week 19 (Phase IV).   Conclusion: The physiotherapy rehabilitation process, in this case, focuses on maintaining and increasing the strength of the core muscles and lower extremities, preparing the patient to jog, and training the patient's brain coordination through agility training. Returning to futsal is the ultimate goal of physiotherapy rehabilitation in this case.